The quantitation of carbamino adduct formation of angiotensin II and bradykinin. - Wittebort, R J (1978)
The two equilibrium constants that define the extent of carbamino adduct formation with amines for all values of pH and PCO2 are determined for the alpha-amino groups of the peptide hormones angiotensin II(AII) and bradykinin (BK) by nuclear magnetic resonance techniques. From these constants the variation of carbamino adduct formation has been calculated over the pH range 6.60--8.00 with variable PCO2, and the results are superimposed upon standard pH-bicarbonate diagrams. PCO2, and the results are superimposed upon standard pH-bicarbonate diagrams. The mole fraction, Z, of carbamino adduct form of AII or BK shows a maximum variation in going from metabolic alkalosis, Z congruent to 0.30, to metabolic acidosis, Z congruent to 0.02, with Z near 0.2 for normal acid-base conditions. Adduct formation to hormone may alter the biological effect of the hormone (a) by limiting proteolysis, particularly at the amino-terminal, (b) by altering hormone binding affinity to specific receptors, or (c) by converting the hormone to an antagonist which binds to receptor but does not activate subsequent metabolic events. The requirements for any of these mechanisms to operate are examined in terms of simple equilibrium considerations, and experimental evidence of inhibition of an aminopeptidase model system is presented. These results are consistent with the hypothesis that regulation of some physiological processes through formation of carbamino adduct of peptide hormones is possible.